Effects of Transactional Analysis Method on Senior Secondary School Students Ability to Appreciate Poetry in Jos North, Plateau State, Nigeria - Okwor, Irene Nkasiobi; Chidiebere, Grace Raymond (NIU Journal of Social Sciences, 2021)
The study was set to establish the effects of Transactional Analysis Method of teaching poetic devices on senior secondary students’ ability to appreciate poetry in Jos North, Plateau State. The research was motivated by the poor performance of senior students in poetry appreciation. One research question and one hypothesis guided the study. The study was a pure experimental design that employed randomised pre-test post-test control group design that provided complete control for all sources of internal invalidity and established statistical equivalence of all the samples. The population comprised 1,157 literature students in the 20 government owned public schools in Jos North. The sample was made up of 120 students randomly selected and assigned to experimental and control groups. Poetry Appreciation Test (PAT) made up of objective and essay test items covering theme, sound, imagery, emotions aroused by poems and students’ ability to express their opinions about given poems was used to collect the data and was analysed using mean and standard deviation. Pre-test results showed that the students were not able to respond to the different aspects of poetry appreciation before treatment. The hypothesis was analysed using ANOVA statistics. The result showed that there was a significant difference between the mean scores of the experimental and control groups in poetry appreciation after treatment. Based on the findings it was recommended that transactional analysis method should be adopted by literature teachers to teach poetic devices, literary techniques and poetry appreciation. Keywords: Poetry, Transactional Analysis Method, Poetic Devices, Poetry Appreciation